UTILIZATION OF WASTE PETUNG BAMBOO PIECES AS PARTIAL SUBSTITUTION OF COARSE AGGREGATE TO IMPROVE COMPRESSIVE STRENGTH OF CONCRETE - DOHAR SINABUTAR; YONAS PRIMA ARGA RUMBYARSO (CV KULTURA DIGITAL MEDIA, 2024)
Utilizing waste as an alternative building material is becoming an effective solution to environmental problems and is popular in developing countries. On the other hand, the concrete industry, a key component of construction, continues to innovate to improve quality and efficiency. The increasing demand for concrete is driving the development of mix designs that meet stringent quality and compressive strength standards, while taking into account environmental sustainability. Advances in concrete technology spur research initiatives to improve its quality and efficiency of use, with innovations in material selection and execution methodologies. This is aimed at meeting the increasing needs and overcoming construction challenges. Modern concrete is required to perform optimally in less time, requiring effective additives for performance enhancement. Recent research has integrated bamboo waste from the handicraft industry as a component of concrete mixes, increasing the speed of project execution and providing a sustainable solution in waste management. The authors were interested in conducting an in-depth study on increasing the compressive strength of concrete by integrating waste bamboo pieces. The concrete under study has the following grades f´c 25 MPa (K-300) and tested at 7, 14, and 28 days to assess the effectiveness of bamboo as an additive. The test results are expected to provide significant data on the viability of bamboo waste as a partial substitution for coarse aggregate. The title of the study, “Use of Waste Bamboo Pieces as Partial Substitution for Coarse Aggregate to Increase the Compressive Strength of Concrete,” reflects the objectives of the study and the utilization of sustainable materials in modern construction. Based on the results of the research that has been carried out and the discussion in the previous chapter with the variation of waste bamboo pieces 0%, 10% and 15%, the conclusions can be drawn, namely as follows the results of compressive strength testing on normal concrete at the age of 28 days reach 452 kN (fʹc 26,1 MPa = 104%), while variation 1 of 10% waste bamboo cuttings experienced a decrease in compressive strength, reaching 305 kN (fʹc 17,60 MPa = 70%), and variation 2 15% waste bamboo cuttings decreased, reaching 309 kN (fʹc 17.83 MPa = 71%).